Engineering Mechanics Volume 1: Equilibrium - Hartsuijker, C.; Welleman, J. W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This is the first of two volumes introducing structural and continuum mechanics in a comprehensive and consistent way. The current book, Volume 1: Equilibrium, presents all theoretical developments both in text and by means of an extensive set of figures. This same approach is used in the examples and problems, of which a generous amount have been provided to aid understanding and practice. The book consists of distinct modules, each divided into sections which are conveniently sized to be used as lectures. Both formal and intuitive (engineering) arguments are used in parallel to derive the principles used, for instance in bending moment diagrams and shear force diagrams. A very important aspect of this book is the straightforward and consistent sign convention, based on the stress definitions of continuum mechanics. This method has been tried and tested over a number of years, and has been used for introductory courses at Delft University of Technology in the faculties of Civil Engineering, Aeronautical Engineering, Industrial Design and Architectural Engineering.
Statics of a Particle -- Statics of a Rigid Body -- Structures -- Calculating Support Reactions and Interaction Forces -- Loads -- Gas Pressure and Hydrostatic Pressure -- Earth Pressures -- Trusses -- Section Forces -- Mathematical Description of the Relationship between Section Forces and Loading -- Bending Moment, Shear Force and Normal Force Diagrams -- Calculating M, V and N Diagrams -- Cables, Lines of Force and Structural Shapes -- Virtual Work -- Influence Lines.
Keywords: ENGINEERING; MECHANICS, APPLIED; MATERIALS; MECHANICAL ENGINEERING; ENGINEERING; THEORETICAL AND APPLIED MECHANICS; CONTINUUM MECHANICS AND MECHANICS OF MATERIALS; STRUCTURAL MECHANICS